Emerging Drugs for Uveitis - Larson, Theresa (2011)
IMPORTANCE OF THE FIELD: Uveitis is a challenging disease covering both infectious and noninfectious conditions. The current treatment strategies are hampered by the paucity of randomized controlled trials (RCTs) and few trials comparing efficacy of different agents. AREAS COVERED IN THIS REVIEW: This review describes the current and future treatments of uveitis. A literature search was performed in PUBMED from 1965 to 2010 on drugs treating ocular inflammation with emphasis placed on more recent, larger studies. WHAT THE READER WILL GAIN: Readers should gain a basic understanding of current treatment strategies beginning with corticosteroids and transitioning to steroid sparing agents. Steroid sparing agents include the antimetabolites which include methotrexate, azathioprine, and mycophenolate mofetil; the calcineurin inhibitors which include cyclosporine, tacrolimus; alkylating agents which include cyclophosphamide and chlorambucil; and biologics which include the TNF-α inhibitors infliximab, adalimumab, and etanercept; daclizumab, interferon α2a, and rituximab. TAKE HOME MESSAGE: Newer agents are typically formulated from existing drugs or developed based on new advances in immunology. Future treatment will require a better understanding of the mechanisms involved in autoimmune diseases and better delivery systems in order to provide targeted treatment with minimal side effects.